A Critique on the Book Postmodernism: Skepticism and Socialism from Rousseau to Foucault - Shamsol Muluk Mostafavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In Explaining Postmodernism book, Stephen R. C. Hicks examines the historical and intellectual roots of the postmodern movement and shows the influence of Rousseau, Kant, and other philosophers on its creation and growth. From the position of defending the West and the capitalist system, he attacks hard on the postmodern current. He considers it the first coherent and decisive expression of anti-rationalism from Kant onwards and counts for its consequences such as metaphysical anti-realism, epistemological mentality, getting the feeling in the heart of value propositions, and as a result, relativism in the field of knowledge and value and underestimation of scientific work, and etc. The present article intends to critique Hicks' views while providing a summary of his views. An attempt will be made to show how Hicks's view on the unequivocal acceptance of the capitalist order influenced his report of the origins of postmodernism and the current state of the movement, leading to a reductionist and partisan analysis on his side.